The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3748/wjg.v13.i30.4108
|View full text |Cite
|
Sign up to set email alerts
|

Detection and treatment of synchronous lesions in colorectal cancer: The clinical implication of perioperative colonoscopy

Abstract: AIM:To evaluate the clinical significance of preand intra-operative colonoscopy for the detection of synchronous lesions in colon cancer. METHODS:Two hundred and sixty-five pre-operative and 51 intra-operative colonoscopic evaluations were performed in 316 colorectal cancer patients who underwent curative resection from January 2001 to June 2006. The incidence and characteristics of synchronous lesions and their influence on surgery were evaluated. RESULTS:Two hundred and eighty-two synchronous lesions were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…It is difficult to identify certain small tumors on CT, and sometimes complete examination of the large intestine cannot be conducted, due to intestinal lumen stenosis. The combined use of CT and colonoscopy has been reported as a useful tool for the preoperative evaluation of synchronous colorectal carcinoma (15,16). Colonoscopic examination may provide clear images of the whole colon.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to identify certain small tumors on CT, and sometimes complete examination of the large intestine cannot be conducted, due to intestinal lumen stenosis. The combined use of CT and colonoscopy has been reported as a useful tool for the preoperative evaluation of synchronous colorectal carcinoma (15,16). Colonoscopic examination may provide clear images of the whole colon.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al did not observed any complications in 58 patients, in case of whom they performed intraoperational colonoscopy (13). Studies by Korean scientistKim, in case of 265 patients, who had colonoscopy performed during surgical procedure, a disjunction of intestinal anastomosis was observed in 1 patient (1.5%) and wound infection was observed in 3 patients (7.14%) (20). Brullet et al observed only two cases of complications (2.98%), lying in mucosa injuries (10).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of synchronous tumors in the colon ranges from 1.5 to 9% (average 5%) (12,13). Adenomatous polyp or polyps accompany primary colorectal tumors in 15-50% (14). Therefore, the entire colon should be endoscopically evaluated prior to surgery for colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%